A study of clinical presentations and management of cholelithiasis - Kumar B., Sathish; Reddy, Venkat; Reddy V., Suryanarayana; C., Ram Mohan; Koneru, Jahnavi (International Surgery Journal, 2019)
Background: Cholelithiasis or gallstones, is one of the most common and costly of all the gastrointestinal diseases. Gallstones are associated with high-calorie diets, type 2 diabetes mellitus, dyslipidemia, hyperinsulinism, obesity, and metabolic syndrome. The aim of the study was to analysis the incidence, clinical presentations, and management of cholelithiasis in tertiary care Hospital at Karimnagar, Telangana, India. Methods: This study was a prospective study; total 50 patients were enrolled in this study. The study was conducted at Department of Chalmeda Anand Rao Institute of Medical Sciences, Karimnagar from September 2016 to September 2017. The data were analyzed and evaluated for clinical profile, management options of cholelithiasis. Results: The present study shows gallstones diseases are a common problem in female population. The female to male ratio is 3:2. Age, gender and incidence statistically there was no significant in this study. Conclusions: Gallstones analysis showed mixed stone in 90% of the cases and cholesterol stones in 8% of the cases as the most common variety. The period of post-operative stay in our study was 7 days for open cholecystectomy and 3 days for laparoscopic cholecystectomy in majority of the cases.